2022
DOI: 10.3389/fpsyg.2022.900806
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Pre-service Teachers’ Intentions to Use Technology-Enabled Learning: An Extended Model of the Theory of Planned Behavior

Abstract: This study proposed an extended theory of planned behavior (TPB) to examine the factors that influence pre-service teachers’ intention to use technology-enabled learning, using constructivist pedagogical beliefs (CPB) and information and communication technologies (ICT) competencies as antecedent variables for attitudes, subjective norms (SNs), and perceived behavioral control. An online study was conducted with a random sample of pre-service teachers from 7 universities in China, and 811 validated questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 62 publications
0
2
0
1
Order By: Relevance
“…This finding aligns with previous research conducted by Crawley [69], which demonstrated the influential role of subjective norms in shaping science teachers' intention to adopt research-based teaching methods. Moreover, recent studies conducted by Hou et al [70] have further emphasized the promotional effect of subjective norms on pre-service teachers' attitude toward the utilization of technologyenabled learning. Subjective norms reflect the social acceptance and recognition of online teaching, indicating society's attitude and perceptions toward online teaching [71], which, in turn, further affect teachers' attitude toward online teaching and behavioral intention for online teaching.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with previous research conducted by Crawley [69], which demonstrated the influential role of subjective norms in shaping science teachers' intention to adopt research-based teaching methods. Moreover, recent studies conducted by Hou et al [70] have further emphasized the promotional effect of subjective norms on pre-service teachers' attitude toward the utilization of technologyenabled learning. Subjective norms reflect the social acceptance and recognition of online teaching, indicating society's attitude and perceptions toward online teaching [71], which, in turn, further affect teachers' attitude toward online teaching and behavioral intention for online teaching.…”
Section: Discussionmentioning
confidence: 99%
“…El siguiente clúster se enfoca en las creencias, actitudes que influyen en la intención de uso de TICs en los procesos de enseñanza aprendizaje. Aunque los artículos se enfocan principalmente en los docentes (Harmandaoğlu Baz and Cephe 2022; Hou et al 2022;Zimmermann, Melle, and Huwer 2021), otros lo hacen en lo estudiantes.…”
Section: Análisis De Las Palabras Claveunclassified
“…In the online learning-related study, home-based learning positively affected students' attitudes (Zhao et al, 2022). Hou et al (2022) explored the function of constructivist pedagogical beliefs (CPB), and information and communication technologies (ICT) competencies as antecedent variables for the three determinants of TPB. Cognitive and motivational factors were also proved to be the essential predictors of three determinants of TPB (Pan et al, 2023).…”
Section: Tpb In the Educational Contextmentioning
confidence: 99%